Secondary Hemophagocytic Lymphohistiocytosis: A Challenging Diagnosis in a Patient with Autoimmune Hepatitis - Colin Casault; Juan G. Posadas-Calleja (Case Reports in Critical Care)
Background. We describe a case of secondary Hemophagocytic Lymphohistiocytosis (HLH) from autoimmune hepatitis mimicking severe sepsis in a man admitted to the intensive care unit. Case Presentation. A 34-year-old Pakistani male with a prior history of biopsy-proven autoimmune hepatitis presented to a regional hospital with severe fever, cytopenias, hyperferritinemia, hypertriglyceridemia, splenomegaly, and a bone marrow biopsy showing hemophagocytosis. After ruling out mimicking conditions, a diagnosis of HLH was made using the HLH-2004 diagnostic criteria. He was treated with dexamethasone and etoposide, without bone marrow transplantation (BMT) due to poor functional status. At one-year after follow-up, he had returned to his baseline functional status without recurrence. Conclusion. We describe a rare case of secondary HLH in the setting of autoimmune hepatitis. Broadly, this case report educates clinicians to consider this potentially missed diagnosis. This case also informs clinicians that treatment of secondary HLH with BMT may not be necessary for the management of secondary HLH due to autoimmune hepatitis. Finally, it provides a detailed description of the natural history of a single patient with secondary HLH due to autoimmune hepatitis.